Pretografias: uma poética com a comunidade remanescente de quilombo três irmãos - Nascimento, José Lucas Araújo do (2021)
This research aims to discuss the processes of invention, production, and experience of Pretographies as poetics of creation in/with art in the Remaining Community of Quilombo Três Irmãos - located in Croatá-CE. The methodological organization of the research establishes a dialogue with cartography, according to Passos and Barros (2015), tracing the emergence of a decolonial poetic image, which is also thought of with the Somatic Performative Research method developed by Fernandes (2015). To that end, the text is divided in three parts: “Pretografias: poética-processo”, “Pretografias: pele-cascas”, and “Pretografias: pele-poeira”. The first one, “Pretografias: poética-processo”, provides an overview of how the concept of Pretografias is designed and it is presented through the photoperformance “Pele Preta” (Black Skin), a pretographic experience, which its creation process takes place through writings in the skin itself, dialoguing with the concept of "escrevivência" by Conceição Evaristo. The second part, “Pretografias: pele cascas”, proposes a creation experience with community members based on visual compositions made with the paint from the bark of trees. The third part “Pretografias: pele-poeira”, re-signified, narrates aspects of the historical, social and cultural context of the aforementioned quilombola community, pointing out, moreover, the tensions of regulation (GOMES, 2011), which stem from the coloniality of power, knowledge and being (MIGNOLO, 2010) that cross the emancipatory knowledge of black corporeality. The main theoretical contribution of this research, as the consolidation of a knowledge that must be established beyond the hegemonic epistemologies, was: Sílvio Almeida (2019), Conceição Evaristo (2018), Djamila Ribeiro (2017), Mbembe (2018), Patricio Guerrero Arias (2010).